DESAIN GAMBAR ALAT PELEPAS BAN SEPEDA MOTOR DENGAN SOFTWARE AUTOCAD - Amin Nur Akhmadi (University of Muhammadiyah Jakarta, 2019)
The development of science and technology covers all fields and has a huge impact on society. Technology demands will bring people to think of creating something new. One of the human creations that is an important part of human life is machines, these machines have many models, shapes and benefits, one of which is a motor vehicle tire removal and installation machine, in general the motorized tire removal and installation machines are widely used in small and medium enterprises, the main drivers are usually using air pressure or pneumatics. The objective to be achieved in this research is to realize the design of a motorcycle tire release tool with the AutoCAD 2012 software. By designing a drawing design to release a motorcycle tire, and a tool support frame. The Planning Stage by determining the title and subject matter and software needed and then making the plot, the implementation phase begins to determine the frame design, then designs the framework and documents the activities carried out during the research. Checking the validity of the data Checking the validity of the data is done by displaying the results of the design of motorcycle tire release machines in accordance with the research plan. Analysis of research data is by collecting data, reducing data, presenting data. Preparation of this stage report all documentation collected and compiled into a research report. The design results are chuck, bottom frame, release hook arm, release hook, release device design with installed wheels, conclusions Concave wheel rim clamp has three sides that serve to clamp to all sides of the rim, each clamping clamp has a stretch setting on each side.